Proceedings of the 29th Annual Symposium on User Interface Software and Technology 2016
DOI: 10.1145/2984511.2984578
|View full text |Cite
|
Sign up to set email alerts
|

IdeaHound

Abstract: Prior work on creativity support tools demonstrates how a computational semantic model of a solution space can enable interventions that substantially improve the number, quality and diversity of ideas. However, automated semantic modeling often falls short when people contribute short text snippets or sketches. Innovation platforms can employ humans to provide semantic judgments to construct a semantic model, but this relies on external workers completing a large number of tedious micro tasks. This requiremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Experimental research confirms that showing users similar ideas and comb ining them to build additional ones can be beneficial and inspirational in the idea generation process (Siangliulue et al, 2016). Thus, collaboration during the ideation process will be helpful in repeatedly generating enhanced qualitative ideas over time.…”
Section: Figure 2 Recommendation In Smart Organizationmentioning
confidence: 52%
“…Experimental research confirms that showing users similar ideas and comb ining them to build additional ones can be beneficial and inspirational in the idea generation process (Siangliulue et al, 2016). Thus, collaboration during the ideation process will be helpful in repeatedly generating enhanced qualitative ideas over time.…”
Section: Figure 2 Recommendation In Smart Organizationmentioning
confidence: 52%
“…(92%, 131 publications), with most intended for use on a laptop or personal computer (52%, 75 publications). These include both web-based and standalone applications, e.g., IdeaHound [159], aimed at supporting creativity through semantic modelling of the spatial structure of a solution space. CSTs intended for miscellaneous or specialized devices that do not fit into our main device categories account for ∼25% of our sample (36 publications).…”
Section: Devices Supportedmentioning
confidence: 99%
“…For example, we can highlight in the UI untapped IoT categories and devices in the form of visuals similar to a bibliometrics diagram or an Idea Map and encourage crowd-workers to contribute in those categories and devices. This can help to avoid duplication from crowd workers and could lead to a system where a secondary task of feedback (determining the similarity of ideas) can be integrated into the primary task of the scenario generation task (Siangliulue, Chan, Dow, & Gajos, 2016). Nonetheless, this previous study has shown the efficacy of this approach for generating and judging the similarity of short text snippets (e.g., birthday messages).…”
Section: Artificial Intelligence Guiding Crowd Workers For Creative Imentioning
confidence: 99%